M. Brothers Enterprise / Mohd Azrul Md Said... [et al.] - Md Said, Mohd Azrul; Hj Zakaria, Mohd Faez; Zakaria, Mohd Hafeez; Mohamed Anuwar, Mohd Nor; Abd Hamid, Mohd Shahuddin (2000)
M. Brothers Enterprise is a join venture of partnership company that are been managed by five partners that contribute their share. This company is situated at Sungai Petani Industries Estate, Sg. Petani Kedah that will full operate on 1 January 2000. Main activities of this company are producing and supplying casing of radio component.